Tailoring surface nanoroughness of electrospun scaffolds for skeletal tissue engineering. (1st September 2017) - Chen, Honglin; Huang, Xiaobin; Zhang, Minmin; Damanik, Febriyani; Baker, Matthew B.; Leferink, Anne; Yuan, Huipin; Truckenmüller, Roman; van Blitterswijk, Clemens; Moroni, Lorenzo
Graphical abstract: Abstract: Electrospun scaffolds provide a promising approach for tissue engineering as they mimic the physical properties of extracellular matrix. Previous studies have demonstrated that electrospun scaffolds with porous features on the surface of single fibers, enhanced cellular attachment and proliferation. Yet, little is known about the effect of such topographical cues on cellular differentiation. Here, we aimed at investigating the influence of surface roughness of electrospun scaffolds on skeletal differentiation of human mesenchymal stromal cells (hMSCs). Scanning electron microscopy (SEM) and atomic force microscopy (AFM) analysis showed that the surface nanoroughness of fibers was successfully regulated via humidity control of the electrospinning environment. Gene expression analysis revealed that a higher surface roughness (roughness average (Ra) = 71.0 ± 11.0 nm) supported more induction of osteogenic genes such as osteopontin (OPN), bone morphogenetic protein 2 (BMP2), and runt-related transcription factor 2 (RUNX2), while a lower surface roughness (Ra = 14.3 ± 2.5 nm) demonstrated higher expression of other osteogenic genes including bone sialoprotein (BSP), collagen type I (COL1A1) and osteocalcin (OCN). Interestingly, a lower surface roughness (Ra = 14.3 ± 2.5 nm) better supported chondrogenic gene expression of hMSCs at day 7 compared to higher surface roughness (Ra = 71.0 ± 11.0 nm). Taken together, modulating surface roughness of 3D scaffolds appears to be a significant factor in scaffold design for the control of skeletal differentiation of hMSCs. Statement of Significance: Tissue engineering scaffolds having specific topographical cues offer exciting possibilities for stimulating cells differentiation and growth of new tissue. Although electrospun scaffolds have been extensively investigated in tissue engineering and regenerative medicine, little is known about the influence of introducing nanoroughness on their surface for cellular differentiation. The present study provides a method to engineer electrospun scaffolds with tailoring surface nanoroughness and investigates the effect of such topographical cues on the process of human mesenchymal stromal cells differentiation into osteoblasts and chondrocytes linages. This strategy may help the design of nanostructured scaffolds for skeletal tissue engineering.